LINGUISTIC ABILITY AS A KEY COMPONENT OF FOREIGN LANGUAGE COMMUNICATIVE COMPETENCE (Conference Zone, 2021)
This article discusses to identify which components of linguistic competence are underdeveloped among students and which ones are slow to develop or not develop at all, as well as the lexical-grammatical component of linguistic competence that determines a student's ability to use certain lexical units in the grammatical field